The generic framing procedure (GFP) an overview. - Hernandez-Valencia, E. (IEEE Communications magazine)
The Generic Framing Procedure (GFP) is a standardized traffic adaptation protocol for broadband transport applications. It provides an efficiency and QoS-friendly mechanism to map either a physical layer or logical link layer signal to a byte-synchronous channel. It also supports basic client control functions for client management purposes. This article presents a brief overview of GFP.